Assessment of the Effectiveness of Health Education for Ibs Women by Examining the Frequency and Disturbance of Gi Symptoms, Quality of Life and Days of Drug Use - Lin, Hsiu-Chin; Tsao, Lee-Ing (European Scientific Journal, ESJ, 2018)
Background: Irritable bowel syndrome (IBS) is a common and chronic functional disorder, yet few studies have demonstrated the effects of IBS health education. Methods: This study was conducted at the gastrointestinal (GI) clinic of a hospital. A parallel-design control trial for IBS women, in which health education was implemented via individual instruction and the Self-Care Manual for IBS Women, was carried out. The questionnaire utilized in this study covered three areas, namely IBS symptom disturbance and frequency, quality of life, and days of drugs use. The intervention effects were assessed four weeks and eight weeks after the intervention and estimated using the GLMM model (generalized linear mixed model). Results: The experimental and control groups consisted of 31 and 30 participants, respectively. The assessment indicated that health education intervention had significantly reduced symptom frequency in the experimental group after four weeks (Î² = -2.60, P < 0.01) and after eight weeks (Î² = -3.30, P < 0.01); significantly reduced symptom disturbances after four weeks (Î² = -5.01, P < 0.01) and after eight weeks (Î² = -4.79, P < 0.01). Quality of life for both groups increased after eight weeks, with the experimental group experiencing a greater increase than the control group (Î² = 15.20, P > 0.05). Drug use decreased by an average of 6.23 days (P < 0.01) and 1.3 days (P > 0.05) in the experimental and control groups, respectively. Conclusions: IBS health education had a positive effect on symptom frequency and disturbance, quality of life and days of drug use.